Mindfulness-Based Stress Reduction in Breast Cancer Survivors with Chronic Neuropathic Pain: A Randomized Controlled Trial - Yaadwinder Shergill; Danielle B. Rice; Eve-Ling Khoo; Virginia Jarvis; Tinghua Zhang; Monica Taljaard; Keith G. Wilson; Heather Romanow; Brittany Glynn; Rebecca Small; Joshua A. Rash; Andra Smith; et al. (Pain Research and Management)
Context. Many breast cancer survivors live with chronic neuropathic pain (CNP) after breast cancer treatment. Despite pharmacological management of CNP, many women continue to report disabling pain and reduced quality of life. Addressing pain with psychosocial interventions as an adjunct to pharmacological treatment is often recommended for CNP. Objectives. The purpose of this study was to compare the effects of group-delivered mindfulness-based stress reduction as compared to a waitlist control group among breast cancer survivors living with CNP. Methods. A randomized controlled trial design was applied, and outcomes collected included pain, emotional function, quality of life, and global impression of change. Results. A total of 98 women were randomized and included in analyses. The sample included 49 women in the mindfulness-based stress reduction group, and 49 women in the waitlist control group. The intervention group participants (mean age 51.3 years, standard deviation = 11.4) and waitlist participants (mean age 55.1 years, standard deviation = 9.6) reported an average pain duration of approximately three years. No significant differences were found on the primary outcome of the proportions of women with reduced pain interference scores from the time of randomization to 3 months after the intervention was received. No significant changes were found among secondary outcomes. Conclusion. Our randomized clinical trial did not find significant benefits of group-based mindfulness-based stress reduction for the management of CNP. The current study findings should be replicated and are important to consider given ongoing concerns that nonsignificant results of mindfulness-based stress reduction are often unpublished.